Digital Capitalism Behind the “Broadcast Yourself” Tagline: (Study of Digital Discourse on the Popularity in Indonesia’s YouTube Content Industry) - Febriyanti, Syafrida Nurrachmi; Ida, Rachmah (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Through its phenomenal jargon